1973
DOI: 10.1111/j.1467-9450.1973.tb00092.x
|View full text |Cite
|
Sign up to set email alerts
|

An aggression machine II. Interindividual differences in the aggressive defence responses aroused by varying stimulus conditions

Abstract: PitkÄnen, L. An aggression machine. II. Interindividual differences in the aggressive defence responses aroused by varying stimulus conditions. Scand. J. Psychol., 1973, 14, 65–74.‐The subjects, six aggressive and nonaggressive groups of ten 9‐year old boys, selected by rating method, were tested with an “aggression machine” (PAM) constructed by the writer. The varying stimulus conditions included two situations of impulsive aggression and six variations of specified attackers. The results showed that (1) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Boys who were rated overtly aggressive by their teachers retaliated the provocations of a same-sized peer of the same sex with stronger intensity than other boys did [Pitka¨nen, 1973b]. A similar finding was obtained in a new sample of participants where the 'maladjusted' children displayed more intensive reactions than 'adjusted' children against several attackers [Juuja¨rvi et al, 2001].…”
supporting
confidence: 73%
“…Boys who were rated overtly aggressive by their teachers retaliated the provocations of a same-sized peer of the same sex with stronger intensity than other boys did [Pitka¨nen, 1973b]. A similar finding was obtained in a new sample of participants where the 'maladjusted' children displayed more intensive reactions than 'adjusted' children against several attackers [Juuja¨rvi et al, 2001].…”
supporting
confidence: 73%
“…Further explorations concerning the main factorial determinants of the model as well as its concurrent and predictive validity [Pitkänen, 1973b;Pulkkinen, 1982Pulkkinen, , 1986 have resulted in a modified and more refined version of the model [Pulkkinen, 1995]. As it is presented, it consists of inhibitory and enhancing processes of emotion and behavior and defines four behavioral types: aggressiveness, constructiveness, compliance, and anxiousness.…”
Section: Introductionmentioning
confidence: 99%
“…Insight 5 is that the concurrent validity of the measure of aggression depends on the context of aggression in which it occurs. The PAM study indicated that when the attacker was a boy of the same size, the intensity of reactive aggression correlated significantly with teacher ratings of children's general aggressiveness and low self-control (Pitkänen, 1973b).…”
Section: <Figure 1 Here>mentioning
confidence: 94%